User-Defined Noise-Cancelling Headphones for Personalized Acoustic Experience - Yutong Chen (Innovation in Science and Technology, 2024)
The user-defined noise-cancelling headphone allows users to personalize the noise-cancelling ability of the headphone. This can help them be aware of both the sound and the surroundings. Prototype is still in progress, so is testing.